Differential effects of short-term and long-term ketogenic diet on gene expression in the aging mouse brain - Matthew S. Stratton; José Alberto López-Domínguez; Alessandro Canella; Jon J. Ramsey; Gino A. Cortopassi (The Journal of Nutrition, Health and Aging)
Background: Aging is associated with multiple neurodegenerative conditions that severely limit quality of life and can shorten lifespan. Studies in rodents indicate that in addition to extending lifespan, the ketogenic diet (KD) improves cognitive function in aged animals, yet long term adherence to KD in Humans is poor. Objectives: To broadly investigate what mechanisms might be activated in the brain in response to ketogenic diet. Methods: We conducted transcriptome wide analysis on whole brain samples from 13-month-old mice, 13-month-old mice fed a ketogenic diet for 1 month, 26-month-old mice, and 26-month-old mice fed a ketogenic diet for 14 months. Results: As expected, analysis of differently expressed genes between the old (26 month) vs younger mice (13 month) showed clear activation of inflammation and complement system pathways with aging. Analysis between the 26-month-old animals fed ketogenic diet for 14 months with 26-month-old animals fed control diet indicate that long-term KD resulted in activation of LRP, TCF7L2 (WNT pathway), and IGF1 signaling. There was also a significant increase in the expression of SOX2-dependent oligodendrocyte/myelination markers, though TCF7L2 and SOX2 dependent gene sets were largely overlapping. Remarkably, the effect of 1 month of ketogenic diet was minimal and there was no congruence between gene expression effects of short-term KD vs long-term KD. Conclusions: This work informs target identification efforts for aging and neurodegenerative disorder therapeutics discovery while also establishing differential effects of short-term vs long-term KD on gene expression in the brain.